STRATEGI BISNIS PT. UNILEVER DALAM PERSAINGAN PRODUK KOSMETIK DI INDONESIA TAHUN 2010-2015 - Hafhazah Lavari; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research is examine the Business strategy of PT. Unilever Indonesia to compete its cosmetic product with another cosmetic brand in Indonesia. Multinational Coorperation or MNC is a form of a cooperation which ranged in various field and production and its operations range is went across the market states boundaries. Unilever is one of multinational cooperation that has a rapid developed in Indonesia. PT. Unilever’s production are food, groceries, and cosmetic products.This research is theoretically built by using theory and multinational cooperation concept. Researcher formulate all data from books, journal, encyclopedia, media, and website. Theoritical framework in this research using qualitative methods.This research proves that PT. Unilever Indonesia have a several methods to compete its cosmetics products with another cosmetics brand in Indonesia in 2010-2015. The strategies are, promoting strategy, sustainabilitybased strategy, community engagement strategy, informations technology strategy, fungtional strategy, and competitive profile matrix (CMP) strategy..Keywords : Bussiness strategy, Multinational coorporation, market states boundaries, Multinational cooperation concept